Control of sulphite formation of lager yeast - Wurzbacher, Michael; Franz, Oliver; Back, Werner (BrewingScience, 2005)
On the basis of existing literature, the influences of yeast and pitching parameters on sulphite formation were evaluated in several laboratory, pilot and industrial scale fermentations. The sulphite formation was strongly influenced by the predisposition of the yeast. Additional it was dependent on parameters affecting yeast growth during fermentation such as the physiological state of the yeast and the availability of nutrients and oxygen. The supply of the brewing yeast with nutrients and oxygen was altered by the pitching parameters. It was demonstrated, that the sulphite formation could be controlled by the pitching rate and the aeration rate. Based on the fermentation trials, a model that describes the influence of the pitching parameters using the key figures “extract per yeast cell” and “oxygen per yeast cell” is introduced. It allows the prediction of the effect of variations of aeration, pitching rate and original gravity on sulphite formation during fermentation.